Etiology and Outcome of Acute Liver Failure: Experience from a Liver Transplantation Centre in Montreal - Geneviève Tessier; Edith Villeneuve; Jean-Pierre Villeneuve (Canadian Journal of Gastroenterology)
BACKGROUND: Acute liver failure is a rare condition in which massive liver injury is associated with the rapid development of hepatic encephalopathy. Although viral hepatitis and drug-induced liver injury are the most common causes, no specific etiology is found in a substantial proportion of cases reported from Europe and the United States.